Concurrent Beet Juice and Carbohydrate Ingestion: Influence on Glucose Tolerance in Obese and Nonobese Adults. (19th January 2017) - Beals, Joseph W.; Binns, Scott E.; Davis, Janelle L.; Giordano, Gregory R.; Klochak, Anna L.; Paris, Hunter L.; Schweder, Melani M.; Peltonen, Garrett L.; Scalzo, Rebecca L.; Bell, Christopher
Abstract : Insulin resistance and obesity are characterized by low nitric oxide (NO) bioavailability. Insulin sensitivity is improved with stimulation of NO generating pathways. Consumption of dietary nitrate (N O 3 - ) increases NO formation, via N O 3 - reduction to nitrite (N O 2 - ) by oral bacteria. We hypothesized that acute dietary nitrate (beet juice) ingestion improves insulin sensitivity in obese but not in nonobese adults. 12 nonobese (body mass index: 26.3 ± 0.8 kg/m 2 (mean ± SE)) and 10 obese adults (34.0 ± 0.8 kg/m 2 ) ingested beet juice, supplemented with 25 g of glucose (carbohydrate load: 75 g), with and without prior use of antibacterial mouthwash to inhibit N O 3 - reduction to N O 2 - . Blood glucose concentrations after beet juice and glucose ingestion were greater in obese compared with nonobese adults at 60 and 90 minutes (P = 0.004 ). Insulin sensitivity, as represented by the Matsuda Index (where higher values reflect greater insulin sensitivity), was lower in obese compared with nonobese adults (P = 0.009 ). Antibacterial mouthwash rinsing decreased insulin sensitivity in obese (5.7 ± 0.7 versus 4.9 ± 0.6 ) but not in nonobese (8.1 ± 1.0 versus 8.9 ± 0.9 ) adults (P = 0.048 ). In conclusion, insulin sensitivity was improved in obese but not in nonobese adults following coingestion of beet juice and glucose when oral bacteria nitrate reduction was not inhibited. Obese adults may benefit from ingestion of healthy nitrate-rich foods during meals.